Collateral circulation detected by arterial spin labeling predicts outcome in acute ischemic stroke. (5th September 2022) - Liu, Sangni; Fan, Dandan; Zang, Feifei; Gu, Nan; Yin, Yun; Ge, Xiao; Zhang, Ling; Chen, Xiang; Zhang, Zhengsheng; Xie, Chunming
Abstract : Background: Robust collateral circulation is strongly associated with good outcomes in acute ischemic stroke (AIS). Aims: To determine whether collateral circulation detected by arterial spin labeling (ASL) magnetic resonance imaging could predict good clinical outcome in AIS patients with 90 days follow‐up. Materials and Methods: Total 58 AIS patients with anterior circulation stroke were recruited. Collateral circulation was defined as arterial transit artifact in ASL images. Modified Rankin Scale (mRS), the Barthel Index, and National Institutes of Health Stroke Scale (NIHSS) were employed to evaluate neurological function for the baseline and 90 days follow‐up. The percent changes of these scores were also calculated, respectively. Finally, a support vector classifier model of machine learning and receiver operating characteristic curve were employed to estimate the power of ASL collaterals (ASLcs) predicting the clinical outcome. Results: Patients with ASLcs represented higher rate of good outcome (83.30% vs. 31.25%, p  < .001) and lower follow‐up mRS scores ( p  < .001), when compared to patients without ASLcs. There were significant differences for percent changes of mRS scores and NIHSS scores between these two groups. Further, the presence of ASLcs could predict good clinical outcome (OR, 1.54; 95% CI, 1.10–2.16), even after controlling for baseline NIHSS scores. The SVC model incorporating baseline NIHSS scores and ASLcs had significant predictive effect (accuracy, 79.3%; AUC, 0.806) on clinical prognosis for AIS patients. Discussion: We targeted on the non‐invasive assessment of collateral circulation using ASL technique and found that patients with ASLcs were more likely to have a good clinical outcome after AIS. This finding is of guiding significance for treatment selection and prognostic prediction. Conclusions: Early ASLcs assessment provides a good powerful tool to predict clinical outcome for AIS patients with 90 days follow‐up.